Engineered crystalline polymers for effective contaminant removal from water - Hadiseh Heydari; Heidar Raissi; Afsaneh Ghahari (Scientific Reports)
Abstract Herein, we discuss the structure-function of biomimetic imidazole-quartet substrates (I-quartets) obtained through the adaptive self-assembly of octyl-ureido-polyol structures in polyamide membranes designed as adsorbents. Molecular dynamics (MD) and well-tempered metadynamics simulations are utilized to examine ion contaminants’ adsorption process and dynamic behaviors onto alkylureido-ethylimidazoles with well-defined supramolecular structures. Moreover, the atoms-in-molecules (AIM) analysis identified multiple types of atomic interactions between the contaminant molecules and the substrates. The results demonstrate that I-quartets with hydrophobic tails significantly enhance the adsorption of contaminant species in the aquatic environment. Descriptors involving interaction energies mean square displacement, radial distribution function, root-mean-square deviation, the number of hydrogen bonds, and solvent-accessible surface area are estimated from the simulation trajectories to study this process. The system containing PO4 3– exhibited notable stability, as indicated by data analysis. Electrostatic interactions primarily govern the adsorption process; however, the interaction between the active sites of alkylureido-ethylimidazole-based channels, such as N = C and O = C, and the investigated contaminant species (PO4 3–, NO3 –, NO2 –, and HNO3) can enhance adsorption due to these interactions. In addition, the free energy values for the adsorption process of PO4 3–, NO3 –, NO2 –, and HNO3 contaminants in water are − 604.77, − 532.63, − 461.24, and − 348.62 kJ mol–1, respectively. The obtained results confirm that alkylureido-ethylimidazoles are prominent adsorbents for removing pollutant ions from wastewater, thus contributing to the development of more efficient materials for water purification.